2021
DOI: 10.1101/2021.01.25.21250101
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of diet, activities, environmental exposures and trimethylamine metabolism on alveolar breath compounds: protocol for a retrospective case-cohort observational study

Abstract: BackgroundExhaled breath contains thousands of volatile organic compounds (VOCs) that reflect on biochemical and biophysical activities both outside and within the human body. Breath analysis could provide non-invasive, cost-effective, real time early disease diagnosis and monitoring of therapeutic responses.ObjectivesThe primary objective of this study was to assess the effectiveness of alveolar breath testing in diagnosing idiopathic systemic body and breath odors. Key secondary objectives were to assess if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Inhalation remains the primary route of occupational exposure to PO, notably in industries utilizing it for polyurethane polyols, propylene glycol production, or as a fumigant. The only publicly available report on levels of PO in exhaled human breath (Filser et al, 2008: 0.083-0.3 ppb), holds pivotal significance for analyzing data in the general population, as exemplified in preliminary results of our own study NCT03451994 (Gabashvili, 2021). Findings stress the importance of considering individual variability in response to PO exposure, influenced by factors like sex, dietary preferences, genetics, and physiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhalation remains the primary route of occupational exposure to PO, notably in industries utilizing it for polyurethane polyols, propylene glycol production, or as a fumigant. The only publicly available report on levels of PO in exhaled human breath (Filser et al, 2008: 0.083-0.3 ppb), holds pivotal significance for analyzing data in the general population, as exemplified in preliminary results of our own study NCT03451994 (Gabashvili, 2021). Findings stress the importance of considering individual variability in response to PO exposure, influenced by factors like sex, dietary preferences, genetics, and physiology.…”
Section: Discussionmentioning
confidence: 99%
“…Inhalation remains the primary route of occupational exposure to PO, notably in industries utilizing it for polyurethane polyols, propylene glycol production, or as a fumigant. The only publicly available report on levels of PO in exhaled human breath (Filser et al, 2008: 0.083-0.3 ppb), holds pivotal significance for analyzing data in the general population This significance is further underscored by our own study, which identified higher levels of PO in a subset of environmentally sensitive individuals, suggesting individual metabolic variations that impact PO exposure and toxicity [5,16].…”
Section: Discussionmentioning
confidence: 99%
“…Breath samples were collected and concentrated using the portable Breath Collection Apparatus (BCA) 5.0, originally developed by Michael Phillips and refined over time [6,7]. This device, controlled by a microprocessor, collects alveolar breath onto an adsorbent tube, with collection duration and flow rate settings adjustable on the device.…”
Section: Methodsmentioning
confidence: 99%
“…This study utilized a cross-sectional design and included participants who met the predetermined inclusion and exclusion criteria. The protocol for participant selection and data collection was previously established and published [6]. In 2012-2013, participants attended one in-person data collection session in four cities: Chicago, Illinois; Miami, Florida; New York, New York (USA) and London (UK).…”
Section: Human Subjectsmentioning
confidence: 99%
“…Community-based decentralized clinical trials are still a new concept. Our previous virtual solutions [3][4][5][6] laid the foundation for such studies and showed their potential and importance for the future of healthcare.…”
Section: Rationalementioning
confidence: 99%